Reorganization of Anatomical Connectome following Electroconvulsive Therapy in Major Depressive Disorder. (6th December 2015) - Zeng, Jinkun; Luo, Qinghua; Du, Lian; Liao, Wei; Li, Yongmei; Liu, Haixia; Liu, Dan; Fu, Yixiao; Qiu, Haitang; Li, Xirong; Qiu, Tian; Meng, Huaqing
Abstract : Objective . Electroconvulsive therapy (ECT) is considered one of the most effective and fast-acting treatment options for depressive episodes. Little is known, however, about ECT's enabling brain (neuro)plasticity effects, particular for plasticity of white matter pathway. Materials and Methods . We collected longitudinal diffusion tensor imaging in the first-episode, drug-naïve major depressive disorder (MDD) patientsn = 24 before and after a predefined time window ECT treatment. We constructed large-scale anatomical networks derived from white matter fiber tractography and evaluated the topological reorganization using graph theoretical analysis. We also assessed the relationship between topological reorganization with improvements in depressive symptoms. Results . Our investigation revealed three main findings: (1) the small-worldness was persistent after ECT series; (2) anatomical connections changes were found in limbic structure, temporal and frontal lobes, in which the connection changes between amygdala and parahippocampus correlate with depressive symptom reduction; (3) significant nodal strength changes were found in right paralimbic network. Conclusions . ECT elicits neuroplastic processes associated with improvements in depressive symptoms that act to specific local ventral frontolimbic circuits, but not small-world property. Overall, ECT induced topological reorganization in large-scale brain structural network, opening up new avenues to better understand the mode of ECT action in MDD.